Measuring Average Supraspinatus Tendon Thickness on Musculoskeletal Ultrasound: Variation in Young Adults - Syed Ali Hussain, Anum Khalid, Samina Javed, Zainab Hassan, Nouman Khan, Rabia Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The human shoulder is one of the most mobile joints of the body but it has less stability as compared to the hip joint which is also a ball and socket joint. Aim: To measure average supraspinatus tendon thickness in young adults, and compare the tendon thickness between genders by using musculoskeletal ultrasound. Study design: Cross sectional study. Methodology: A total of 128 healthy young adults were screened for shoulder pathology using Apley scratch test, Empty Can and Full Can test. The measurements were taken in Modified Crass Short Axis View of Supraspinatus Tendon at 5mm, 10mm and 15mm from Bicep Long Head Tendon and Modified Crass Long Axis View of Supraspinatus Tendon at 5mm, 7mm and 10mm from the highest point of humerus. Data was evaluated by using SPSS version 23. All qualitative data was presented in frequency form and quantitative data was in the form of mean ± SD. Results: There was a significant difference in tendon thickness between males and females. In the long axis view males had thicker tendon as compared to females at 5mm and 7mm in the right side whereas in the left side there was difference at 5mm, 7mm and 10mm from the highest point on the humerus. Within gender comparison showed significant difference in tendon thickness measured in short axis as significant tendon thickness difference measured at 5mm, 7mm and 10mm from highest point of humerus. Conclusion: It was concluded that supraspinatus tendon thickness differed significantly in young males and females. Keywords: Musculoskeletal Ultrasound, Supraspinatus Tendon Thickness, Young Adults, Body Mass Index and Rotator Cuff.